Catheter Ablation of Ventricular Tachycardia in the Presence of an Old Endocavitary Thrombus Guided by Intracardiac Echocardiography. Issue 6 (13th April 2016) - PEICHL, PETR; WICHTERLE, DAN; ČIHÁK, ROBERT; ALDHOON, BASHAR; KAUTZNER, JOSEF
Abstract : Background: Catheter ablation of ventricular tachycardia (VT) in patients with structural heart disease (SHD) is effective in prevention of arrhythmia recurrences. However, endocardial ablation may be challenging in the presence of organized left ventricular (LV) endocavitary thrombus. Our goal was to analyze the results of VT ablation in patients with identified old thrombus. Methods and Results: We reviewed clinical and procedural data of 344 consecutive patients who underwent VT ablation for SHD. Old endocavitary thrombus was identified in four patients by preprocedural transthoracic echocardiography (TTE) and in four more patients by intracardiac echocardiography (ICE). All together, the case series of eight patients with detectable thrombus is reported. All patients (one woman, age: 67 ± 7 years) had postinfarction aneurysm (20 ± 8 years after the index myocardial infarction) and the thrombus was well organized without mobile structures. Arrhythmogenic substrate could not be obviously targeted beneath the base of thrombus; however, catheter ablation was successfully performed in the close vicinity. A total of 2.4 ± 1.2 procedures were necessary to abolish VT recurrences. Epicardial ablation was performed in three of eight (38%) patients as a second elective procedure. No procedural or periprocedural complications were observed. During the follow‐up of 14 ± 15 months, two patients (25%) had sporadic VT recurrences. Conclusions: ICE seems to be more sensitive for the detection of LV thrombi compared to TTE and is helpful in real‐time navigation of mapping/ablation catheter. Besides potential thromboembolic risk, large thrombus may prevent accessibility to the "critical" portion of arrhythmia circuit and epicardial ablation is required in selected cases.